1996
DOI: 10.7748/ns1996.04.10.30.32.c6221
|View full text |Cite
|
Sign up to set email alerts
|

General nurses’ attitudes to patients who self-harm

Abstract: This article describes the prevalence of suicidal behaviour, both nationally and in relation to one inner city district general hospital. The authors discuss what is currently known about risk assessment for identifying those patients likely to repeat the act in the near future. They also examine the findings of a recent survey about nurses' perceptions and attitudes to patients who take deliberate drug overdoses. The survey found that nurses possessed some of the facts about risk factors relating to future pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…As knowledge and confidence increased for staff, so too did perceived effectiveness in dealing with self-harming patients. This finding is consistent with international literature (23,34,35). There was also a significant negative relationship between knowledge of self-harm and suicidal behavior and feelings of negativity towards selfharming patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…As knowledge and confidence increased for staff, so too did perceived effectiveness in dealing with self-harming patients. This finding is consistent with international literature (23,34,35). There was also a significant negative relationship between knowledge of self-harm and suicidal behavior and feelings of negativity towards selfharming patients.…”
Section: Discussionsupporting
confidence: 94%
“…The emergence of ''knowledge'' as a principle predictor of perceived effectiveness is consistent with international literature, as is the relationship between ''confidence'' and ''effectiveness'' (23,34,35).…”
Section: Resultsmentioning
confidence: 54%
“…Studies of DSH have shown that multi-professional staff often regard this group as more bdifficult to treat Q and more challenging than other patients [14]. For example, in a survey of 107 nurses, Sidley and Renton [15] reported that 55% of the staff disliked working with DSH patients. Staff attitudes are often reflected in the opinions from DSH patients themselves.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the Nursing Outcomes Classification (NOC) defines a good outcome of nursing care as meaning that a self-mutilating person can refrain from self-mutilation (Johnson, Maas, & Iowa Outcomes Project, 1997). Previous nursing research has focused on the experiences of selfharming adult female inpatients (Lindgren, Wilstrand, Gilje, & Olofsson, 2004;Weber, 2002), and on nurses' attitudes towards self-harming adult patients and clients (McAllister et al, 2002;Sidley & Renton, 1996). Furthermore, untested nursing interventions have been described (Aanderaa & Meling, 2004;Brodtkorb, 2001;Crowe & Bunclark, 2000;Pawlicki & Gaumer, 1993;Sharkey, 2003).…”
mentioning
confidence: 96%